Robust Geographically Weighted Regression Modeling In Cases Of Stunting Toddlers In North Sumatera Utara - Siahaan, Maharani Putri Adam; Husein, Ismail (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Stunting is a problem related to chronic malnutrition that can be caused by inadequate nutritional intake. Stunting is usually found in toddlers aged 12-36 months which is often not realized because usually the difference between normal children and stunted children is not specifically visible. Therefore, researchers want to know the problem of how to model cases of stunted toddlers using Robust Geographically Weighted Regression in North Sumatra. With quantitative research methods, the results obtained were 33 models of the number of cases of stunted toddlers in North Sumatra which were formed using the Robust Geographically Weighted Regression (RGWR) method with a fixed Gaussian kernel weighting function and gave different results for each Regency /City in North Sumatra. Among them is the RGWR mode in Central Tapanuli = 193.2119 + 1.306099 ???? 1 + 0.013863 ???? 2 + 0.000913 ???? 3 – 0.00469 ???? 4 – 0.051564 ???? 5 + ???? and it is obtained that the level of accuracy of the RGWR model is able to provide better estimation results. This is supported by the MAPE value of the RGWR model of 15%, which is in the range of 10% -20%. So the model used is appropriate and effective in estimating the number of cases of stunting toddlers in North Sumatra.